"A Whiter Shade of Pale": Whiteness, Female Beauty Standards, and Ethical Engagement Across Three Cultures. Issue 1 (March 2023) - Mady, Sarah; Biswas, Dibyangana; Dadzie, Charlene A.; Hill, Ronald Paul; Paul, Rehana
Skin color affects women's self-image, a fact that has long been a consequence of racial discrimination and dominance as well as the prevalence of light-skinned models in modern advertisements and other forms of communication. Although not all women aspire to greater whiteness of complexion, this standard has influenced many countries that were once dominated by white invaders. As multiculturalism infuses developed and developing nations, however, these standards may be shifting away from generic and hegemonic visions toward more realistic and varied standards, requiring international marketers to be proactive rather than reactive in their customer engagement practices under the ethical frame of "perfectionism." To examine this perspective, the authors completed a cross-national qualitative study (in-depth interviews) in India, Egypt, and Ghana, where lightness of skin tone has been a culturally imposed prerequisite for women to be considered (and consider themselves) beautiful. Using customer engagement literature and the ethical perfectionism framework, this study investigates women in these countries who embrace or reject this standard, further contextualizing customer engagement research across international markets. Implications are offered as a way to advance multinational corporations' development of customer engagement along a mutually beneficial path.